An Analysis of Students' Reading Comprehension in Narrative Text - Elisa Nur Farihah; Chusnul Chotimah; Ellis Tamela (Channing : Journal of English Language Education and Literature, 2023)
This study was conducted to analyze students' reading comprehension of narrative texts. A qualitative descriptive method with observations, interviews, and documentation is utilized as instruments. The results showed that students had a variety of abilities in understanding narrative texts, from the interviews and existing observational data. Moreover, it was found that 11 students understood this material because they could explain the meaning, cite the examples, mention the general structure, and determine the general structure of narrative texts in the text entitled "Lake Toba." It was also found that four students understood this material quite well, but imperfectly because they did not mention all the general structures of narrative texts; the other five students did not understand this material because, during the interview, they could not explain the meaning, examples, and general structure of this material. based on the student's ability to answer the questions posed by the researcher.